REGULATORY CHALLENGES AND SHARIA COMPLIANCE IN THE OPERATIONAL MANAGEMENT OF TAKAFUL COMPANIES - Alfia Azzuhra; Sunarsih Sunarsih; Azza Ibraisama Ersyada; Taufikur Rohman (Institut Agama Islam Negeri (IAIN) Bone, 2026)
The Islamic insurance (takaful) industry in Indonesia holds significant potential, given the country's dominant Muslim population and the growing Islamic financial ecosystem. Nevertheless, the industry's growth continues to face numerous challenges, particularly with regard to regulation and Sharia compliance. This study aims to analyze the implementation of Sharia compliance in takaful company operations and to identify regulatory challenges that affect the sustainability of the industry. The research employs a qualitative-descriptive approach using library research and normative legal analysis. Data were obtained from legislation, DSN-MUI fatwas, OJK regulations, industry reports, and relevant scientific literature. Analysis was conducted through content analysis, comparative analysis, and qualitative-descriptive analysis. The findings reveal that takaful companies in Indonesia have generally implemented Sharia compliance principles through the use of tabarru' and tijarah contracts, the separation of participant and company funds, and oversight by the Sharia Supervisory Board (DPS). However, the effectiveness of compliance still faces obstacles, including a suboptimal role of the DPS, differences in fatwa interpretation, and the lack of standardized Sharia auditing. From a regulatory perspective, the main challenges include the absence of a dedicated Sharia insurance law, fragmentation of regulations between technical and Sharia authorities, low Islamic financial literacy, limited capital, reduced product competitiveness, slow digital transformation, and the industry's readiness to comply with the Islamic Business Unit (UUS) spin-off policy. Therefore, it is necessary to strengthen the regulatory framework, enhance Sharia governance capacity, and accelerate innovation and digitalization in order to improve the competitiveness and sustainability of the takaful industry in Indonesia.